General characteristics and features of administrative coercive measures in penal institutions - Zlyvko, Stanislav; Sykal, Maksym (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The urgency of considering the application of administrative coercive measures by the staff of the State Criminal and Executive Service of Ukraine is due, on the one hand, to the insufficient theoretical elaboration of this issue, on the other hand to the increasing need of penal institutions in scientific developments aimed at solving specific practical problems.The purpose of the article is to determine and characterize administrative coercion measures in penal institutions on the basis of the analysis of scientific developments and normative-legal acts.Administrative coercion measures in penal institutions are defined and characterized in the article on the basis of the analysis of scientific developments and normative-legal acts. Types of administrative coercion measures, in particular, administrative termination, measures of administrative prevention, measures of administrative termination and measures of administrative responsibility were investigated. The definition of administrative coercive measures applied by the staff of penal institutions was formulated. Namely, it is defined as a set of legally established methods and means used in order to stop illegal behavior of a person violating the law in the field of penal institutions activities, with further involvement of perpetrators to legal liability.Traditionally, administrative coercive measures are divided into preventive measures, coercive measures and liability measures. However, there are other approaches for distributing the administrative coercion measures in the scientific literature. These are measures of administrative termination, measures of administrative prevention, measures of administrative termination and measures of administrative responsibility.It is pointed out that administrative coercion measures make a holistic system in the activities of penal institutions. It includes measures of prevention, termination and responsibility. The main peculiarities of administrative coercion measures in penal institutions are the following: firstly, the subject structure: bodies of the State Criminal and Executive Service of Ukraine (central executive body for executing sentences; territorial governing bodies of the central executive body for executing sentences); penal institutions; other units (paramilitary formations of the State Criminal and Executive Service of Ukraine; bodies of the National Police); secondly, the peculiarities of administrative coercion measures in the activities of the State Criminal and Executive Service of Ukraine include the procedure of application, which combines administrative coercion and criminal-executive activities; thirdly, the application of administrative coercion measures is aimed at ensuring the regime of serving a sentence; fourthly, the use of special means and weapons, as well as the application of various penalties due to the law enforcement nature of a penal institution.